Spatiotemporal distribution of Arctic herbivores in spring: Potential for competition? - Anna Caroline Grimsby; Åshild Ønvik Pedersen; Dorothee Ehrich; Jesper Bruun Mosbacher; Ingrid Marie Garfelt Paulsen; Frida Kristine Brockmann; Virve Ravolainen (Global Ecology and Conservation, 2023)
Biotic interactions are important to the structure and dynamics of food webs and may affect the spatial and temporal distribution of species. In the Arctic, spring snow-cover limits food availability at a critical time for herbivores, potentially leading to resource competition. This study investigates the potential for competition over forage resources during spring in a high-Arctic herbivore community comprising the resident, endemic Svalbard reindeer (Rangifer tarandus platyrhynchus) and Svalbard rock ptarmigan (Lagopus muta hyperborea), and the migratory pink-footed goose (Anser brachyrhynchus) and barnacle goose (Branta leucopsis). First, we investigated herbivore behaviour that could indicate the potential for competition by conducting a field study, and second, we quantified the effects of snow-cover extent, vegetation type and presence of potential herbivore competitors on the spatiotemporal distributions of herbivores using camera-traps in one early and one late snow melt year. Only reindeer and geese appeared with sufficient sample sizes for analysis. The field study revealed that reindeer and geese foraged in the same areas, particularly moss tundra habitats. Although geese were regularly alerted by reindeer, no direct aggressive interactions were observed. The camera-trap study showed that neither of the herbivores significantly affected the spatiotemporal distribution of its potential competitor, but reindeer and goose distribution was instead driven by snow-cover extent and vegetation type. However, the shared space use by these species may lead to different types of interactions, such as facilitation or exploitative competition, which require further assessment, including dietary overlap studies, particularly in the context of climate change-induced shifts in snow melt timing and herbivore abundances.